Morphological and distribution characteristics of \(Halophila beccarii\) Aschers., 1871 in the Cau Hai lagoon, Thua Thien Hue province, Vietnam - Dang, Xuan Thi Le; Phan Thi, Thuy Hang; Ton, That Phap; Truong Thi , Hieu Thao; Hoang, Cong Tin; Luong, Quang Doc (Vietnam Journal of Marine Science and Technology, 2022)
Halophila beccarii Aschers., 1871 was one of the seagrass species that was vulnerable and threatened list by the International Union for Conservation of Nature (IUCN). During the survey period from March 2018 to September 2019, our results showed that H. beccarii was widely distributed in the Cau Hai lagoon and concentrated mainly in the Southeast area of the lagoon. The distribution of H. beccarii was seasonal. The species’ growth started from the early rainy season of the previous year until the end of the dry season of the following year. However, the period when the species had a high cover, biomass, and shoot density was from September 2018 to March 2019, and those values peaked in January 2019. The lowest cover and shoot density were recorded in November 2019, while the lowest biomass was in July 2019. The rainfall had a close positive correlation with the biomass of H. beccarii, while water salinity and water temperature were moderate negatively correlated with the biomass of the species.